2020
DOI: 10.3390/ijerph17186686
|View full text |Cite
|
Sign up to set email alerts
|

Red and Processed Meat Consumption and Risk of Depression: A Systematic Review and Meta-Analysis

Abstract: Depression is one of the leading causes of disability worldwide, with more than 264 million people affected. On average, depression first appears during the late teens to mid-20s as result of a complex interaction of social, psychological and biological factors. The aim of this systematic review with meta-analysis is to assess the association between red and processed meat intake and depression (both incident and prevalent). This systematic review was conducted according to the methods recommended by the Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 76 publications
3
43
0
3
Order By: Relevance
“…A pre-defined, customized spreadsheet was used to extract and collect useful data (Microsoft Excel ® for Windows Redmond, WA, USA, 2007). As carried out before [ 34 ], to reduce methodological heterogeneity and to standardize data extraction, the spreadsheet was pre-piloted by four researchers (V.G., G.S., R.C., A.O.-A.) on 10 randomly selected records.…”
Section: Methodsmentioning
confidence: 99%
“…A pre-defined, customized spreadsheet was used to extract and collect useful data (Microsoft Excel ® for Windows Redmond, WA, USA, 2007). As carried out before [ 34 ], to reduce methodological heterogeneity and to standardize data extraction, the spreadsheet was pre-piloted by four researchers (V.G., G.S., R.C., A.O.-A.) on 10 randomly selected records.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence has pointed towards the involvement of food components in the monoamine synthesis, inflammation processes, regulation of hypothalamic–pituitary–adrenal axis (HPA), and neurogenesis [ 22 ]. A higher consumption of refined and processed foods, as well as high-fat and high-sugar products is associated with higher levels of inflammation and higher risk of depression [ 23 , 24 ]. At the same time, inflammation can be one of the factors implicated in the microvascular dysfunction, which in turn can be responsible for the alterations in brain regional blood flow that were shown to be a risk factor for depression [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a diet full of saturated fat and simple sugar increases oxidate stress, which has been associated with difficulties in attention and concentration [51]. Previous studies have shown the implication of diet on mental health, especially on depression, that indirectly impacts on quality of life, self-efficacy and academic performance [52]. Considering that the Mediterranean diet affects cognitive performance, this statement could explain the beneficial effect that the Mediterranean diet has on self-efficacy, which was found in this study.…”
Section: Discussionmentioning
confidence: 99%